2021
DOI: 10.1021/acsami.1c08468
|View full text |Cite
|
Sign up to set email alerts
|

Rewritable and Tunable Laser-Induced Optical Gratings in Phase-Change Material Films

Abstract: Laser-induced periodic surface structures (LIPSS) can be fabricated in virtually all types of solid materials and show great promise for efficient and scalable production of surface patterns with applications in various fields from photonics to engineering. While the majority of LIPSS manifest as modifications of the surface relief, in special cases, laser impact can also lead to periodic modulation of the material phase state. Here, we report on the fabrication of high-quality periodic structures in the films… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 30 publications
0
18
0
Order By: Relevance
“…In a distinct optical approach, the grating-like spatial characteristics of LSFL can be imprinted in the sub-ablation regime to a phase change material (PCM) such as GeTe [94] or Ge 2 Sb 2 Te 5 [95], allowing the stripes/ridges of the LIPSS to be represented either by the amorphous or by the crystalline phase of the PCM. In this way, by proper choice of the laser irradiation parameters, micron-sized spots with an optically encoded LIPSS patterns can be written and erased again [95,96]. Such optical patterns may be used for information encoding or act as unique safety features.…”
Section: Question 7 Can Lipss Properties Be Modulated/switched Dynamically?mentioning
confidence: 99%
“…In a distinct optical approach, the grating-like spatial characteristics of LSFL can be imprinted in the sub-ablation regime to a phase change material (PCM) such as GeTe [94] or Ge 2 Sb 2 Te 5 [95], allowing the stripes/ridges of the LIPSS to be represented either by the amorphous or by the crystalline phase of the PCM. In this way, by proper choice of the laser irradiation parameters, micron-sized spots with an optically encoded LIPSS patterns can be written and erased again [95,96]. Such optical patterns may be used for information encoding or act as unique safety features.…”
Section: Question 7 Can Lipss Properties Be Modulated/switched Dynamically?mentioning
confidence: 99%
“…Wavelength tunable femtosecond laser sources are highly important in modern science. Research fields like spectroscopy [1][2][3], nonlinear imaging [4][5][6], laser micro processing [7][8][9] and nonlinear optics [10][11][12][13] greatly benefit from high peak and average power wavelength tunable femtosecond pulses, which are often produced using optical parametric amplification (OPA) devices. However, depending on various parameters such as signal wavelength and bandwidth, pump-to-signal conversion efficiency is usually limited to no more than 20% and often substantially less [14].…”
Section: Introductionmentioning
confidence: 99%
“…Although the optical diffraction limit can be reduced by reducing the wavelength of the laser used for direct writing to achieve submicron fabrication, the operation procedure is complicated, with high requirements for fabricating equipment and low fabricating efficiency. Femtosecond laser-induced periodic surface structures (LIPSSs), which are capable of overcoming the diffraction limit, have been widely used in the fabrication of submicron gratings. Vorobyev and Guo reported that different colors were visible on the surface of aluminum with LIPSSs depending on the viewing angle . Bolle, Hiraoka, Dyer, and others have attempted to apply LIPSSs in the direct ablation fabrication of polymers; however, forming a uniform grating on the polymer surface through direct ablation is difficult, and the method therefore does not meet the requirements for optical applications. Recently, Huang et al proposed a nonablative femtosecond laser fabrication technology that greatly improved the uniformity of grating fabricated on a silicon surface; , however, the usability of this technology on flexible substrates has not been further investigated.…”
Section: Introductionmentioning
confidence: 99%